The Interest Rate Exposure of Nonfinancial Corporations - Bartram, Söhnke (Review of Finance, 2002)
Abstract Many interest rates are as volatile as exchange rates and thus represent an equally important source of risk for corporations. While this is true not only for financial institutions, but for other corporations as well, little is known about the interest rateexposure of nonfinancial firms. Consequently, this paper investigates the impact of interest rate risk on a large sample of nonfinancial corporations. It presents empirical evidence for the existence of linear and nonlinear exposures with regard to movements invarious interest rate variables. The interest rate exposure is empirically determinedbymeasures of firm liquidity, but not by financial leverage. JEL classification codes: G3, F4, F3